Rational-Religious Islamic Education Tanet and Its Relevance To Contemporary Islamic Education: Analysis Of Wahid Hasyim's Paradigm - Noviandriani Putri; Zulfatun Ni'mah (Proceeding International Conference on Religion, Science and Education, 2023)
Study this aim for study Genre rational-religious Islamic education Wahid Hasyim 's paradigm in integrate based Islamic education Islamic boarding school with contemporary Islamic Education , which is where the thinking the has bring impact significant to direction development education modern pesantren to moment this . Type study this is library research . The analysis technique covers analysis content and data analysis . Data collection techniques through study later library _ analyzed use method descriptive . Research results this is thinking rational-religious Wahid Hasyim about Islamic education which includes : (1) foundation education boarding school ; (2) Role in development contemporary Islamic education ; (3) Purpose education and (4) curriculum Islamic education based on Wahid Hasyim's perspective integrative- interconnective.